Effect of process variables on the preparation of BSA loaded double-walled poly(lactide-co-glycolide) microspheres - Rahman, Md. Mokhlesur; Ansary, R.H.; Mohamed, Farahidah; Kasmuri, Abdul Razak; Md Aris, Mohd Aznan; Katas, H; Awang, M.B. (2016)
Biodegradable poly(lactide-co-glycolide) (PLGA) microspheres have received much attention over the last twenty-five years for controlled parenteral delivery of therapeutic protein and peptide drugs [1, 2]. In general, for protein drugs delivery, PLGA and PLGA-based single-polymer microspheres system still suffer from two major technical problems associated with their inherent stability problem [3]. Initial burst release followed by very slow and incomplete release is one of the most serious problems in the formulation of PLGA-based protein drugs delivery system. Many strategies have been explored currently to reduce the high initial burst release of protein and peptide drugs from PLGA microspheres [4]. Fabrication of double-walled microspheres in which protein drugs encapsulated in the inner core surrounded by a drug free outer polymer layer offers a promising technique in reducing the high initial burst release. In previous studies, large size double-walled microspheres have been prepared using poly(L-lactic acid) (PLLA) and different co-polymers of PLGA (ester-terminated and carboxyl-terminated) as the core and shell material. Double-walled microspheres consisting PLLA and ester-terminated PLGA as the core or shell material required more time for the complete release of encapsulated drugs due to the slow degrading nature of these polymers.